Impact of contaminated fluid on the working performances of hydraulic directional control valves - Karanović, Velibor (Strojniški vestnik, 2019)
The study aims to investigate the impact of solid particles on the directional hydraulic valve operation. Experiments have been performed for a certain number of operating cycles to measure the impact of the working fluid cleanliness level on the intensity of the wear on contact surfaces as well as on other failures in the operation of the directional control valve. For experimental purposes, a mechanically actuated control valve 4/2 is used. The wear intensity of working elements was determined for different levels of oil contamination by solid particles. Also, experimental results have shown that there are differences between theoretically calculated and the measured flow through the radial clearance. By measuring pressure drop values during the fluid flow through the valve, it was found that oils with the lowest cleanliness level have a greater dispersion of the measured values. The results will contribute to better understanding the impact of working fluid cleanliness on possible defects and failures happening inside hydraulic system components.
Keywords: condition monitoring; čistoča fluida; hidravlični sistemi; hydraulic systems; nadzor stanja; obraba; trdni delci; tribologija; tribology; wear